Academic Productivity and the Changing Research Funding Models in Australia: What is the True Picture? - Marinova, Dora; Newman, Peter (Modelling and Simulation Society of Australia and New Zealand, 2005)
It has become usual practice for the Australian Federal Government to shape the country’s research priorities to better reflect and care for the needs of the economy, society and the physical environment where they exist. The funding mechanisms for university research and research training have also changed with the latest system being introduced since 2001. A new model, namely the Research Quality Framework (RQF) is being currently discussed, shaped along the lines of the British Research Assessment Exercise and the New Zealand’s Performance Based Research Fund. These are also times when the performance of Australian universities is being attacked with open calls for them to prove that they are worth the taxpayers’ money. The paper analyses the productivity of the Australian academic sector between 1992 and 2005 in comparison with New Zealand and the UK (see Figure 1) and then uses the case study of the Institute for Sustainability and Technology Policy (ISTP). Murdoch University to demonstrate the changes in research quality. Its main argument is that the constantly improving performance of the Australian universities is not being acknowledged and instead, a false public image of lack of productivity is being created. Data on research publications is used to show that Australia outperforms the UK and New Zealand whose systems are being used as the model for the proposed changes in Australia. The gap has in fact widened since their reforms were introduced. Further data is provided on different citation systems, research funding and PhD completions in ISTP to demonstrate productivity gains during the period under question.Serious questions can be asked as to the sustainability of the proposed changes. A country with a long-term vision for the future should use universities as a social pillar, which can guarantee brighter prospects for its future generations. For Australia to have a strong and world-class university research sector, adequate resources should be provided to match its current achievements and facilitate the transition to any new funding model. Also, such a new model should allow for diversity and flexibility to properly reflect the complexity of the academic world.